Comparative study of colpocitograma and ninfocitograma in pregnant and nonpregnant - Kanashiro, Alejandro (2015)
The comparative study between ninfocitograma colpocytology and 200 women, comprising 100 pregnant women in the three trimesters of pregnancy and 100 women with normal sexual cycle was performed. The sheets were examined, it counted 200 cells for each extended and was drawn graphs in relation to pictónico rate and maturity value found in the colpocitograma and the ninfocitograma in the 400 extended. These indices were very similar, so it is concluded that the ninfocitograma can successfully replace colpocitograma.